Motivasi Humor dan Aspek Kebahasaan dalam Film Kapal Goyang Kapten Karya Raymond Handaya - Ira Mayasari (Neolectura, 2022)
The purpose of this research is to find out and describe motivations the humor act and technique, as well as linguistic aspets in the Kapal Goyang Kapten movie. This study uses a qualitative descriptive method with the technique of observing and taking notes. The results of this research are unitended humor and intended humor. But, the result that dominated is intended humor. The technique is dominated by ridicule, namely humorous techniques that are intentional and usually aim to ridicule, riddle, and so on. The linguistic aspects found in this study are reasoning as a support for humor, word game puzzles, and phonological word games.